Bedhaya Retnatama Dance In Kraton Surakarta Hadiningrat: A Study Of Form And Its Correlation To Javanese Women's Emancipation (Universitas Negeri Semarang, 2022)
Bedhaya Retnatama dance is one of the classical dances from the Surakarta Hadiningrat Palace which was created directly by one of the king's daughters, GKR Koes Moertiyah Wandansari during the inauguration of the Surakarta Hadiningrat Palace Museum. The purpose of conducting this research is to find out how the form of the performance of the Bedhaya Retnatama Dance and its correlation to the value of Javanese women's emancipation, which is seen as a whole through several main elements and dance supporters. This study uses qualitative methods which are described descriptively in accordance with field conditions using data collection techniques in the form of observation, interview, and documentation methods. The results of the study show that the form of the performance of the Bedhaya Retnatama Dance includes classical dance in the style of the Kraton Surakarta Hadiningrat which has a meaning regarding women's emancipation. Bedhaya Retnatama dance has three major parts, namely: the beginning; the middle / content; and the final part, as well as the middle/content part which is still divided into three parts, namely: maju beksan; beksan; and mundur beksan. The Bedhaya Retnatama dance is danced by nine female dancers who have gone through a long selection and training within the internal scope of the Surakarta Hadiningrat Palace. The purpose of conducting this research is expected to be used as a medium for educating women, especially Javanese women, in behaving and making decisions in life.